Towards a Theoretical Re- Interpretation of the Socioeconomic Challenges of Contemporary Climate Policies - Barreto, Eduardo Sá (Sustainability in Debate, 2014)
The creation of the Intergovernmental Panel on Climate Change (IPCC) marks the beginning of an era of growing importance of environmental issues within energy policy. Initiatives towards emissions intensity reduction are now a general tendency in the mitigation efforts among countries that are the main emitters. Taking the energy efficiency policies as the central point of our discussion, we intend to provide the foundations for a new understanding of the nexus between energy efficiency and energy consumption - based on Marxian theory of value - as well as a new framing for the rebound effect and its relevance to environmental issues.